Early Growth Response Gene 2-Expressing CD4+LAG3+ Regulatory T Cells: The Therapeutic Potential for Treating Autoimmune Diseases - Okamura, Tomohisa; Yamamoto, Kazuhiko; Fujio, Keishi (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are necessary for the maintenance of immune tolerance. Tregs are divided into two major populations: one is thymus-derived and the other develops in the periphery. Among these Tregs, CD4+CD25+ Tregs, which mainly originate in the thymus, have been extensively studied. Transcription factor Foxp3 is well known as a master regulatory gene for the development and function of CD4+CD25+ Tregs. On the other hand, peripherally-developed Tregs consist of distinct cell subsets including Foxp3-dependent extrathymically developed Tregs and IL-10-producing type I regulatory T (Tr1) cells. LAG3 and CD49b are reliable cell surface markers for Tr1 cells. CD4+CD25-LAG3+ Tregs (LAG3+ Tregs) develop in the periphery and produce a large amount of IL-10. LAG3+ Tregs characteristically express the early growth response gene2 (Egr2), a zinc-finger transcription factor, and exhibit its suppressive activity in a Foxp3-independent manner. Although Egr2 was known to be essential for hindbrain development and myelination of the peripheral nervous system, recent studies revealed that Egr2 plays vital roles in the induction of T cell anergy and also the suppressive activities of LAG3+ Tregs. Intriguingly, forced expression of Egr2 converts naïve CD4+ T cells into IL-10-producing Tregs that highly express LAG3. Among the 4 Egr gene family members, Egr3 is thought to compensate for the function of Egr2. Recently, we reported that LAG3+ Tregs suppress humoral immune responses via TGF-β3 production in an Egr2- and Egr3-dependent manner. In this review, we focus on the role of Egr2 in Tregs and also discuss its therapeutic potential for the treatment of autoimmune diseases.